Application of fuel cell and electrolyzer as hydrogen energy storage system in energy management of electricity energy retailer in the presence of the renewable energy sources and plug-in electric vehicles. (15th March 2017) - Nojavan, Sayyad; Zare, Kazem; Mohammadi-Ivatloo, Behnam
Highlights: Electricity retailer determines selling price to consumers in the smart grids. Real-time pricing is determined in comparison with fixed and time-of-use pricing. Hydrogen storage systems and plug-in electric vehicles are used for energy sources. Optimal charging and discharging power of electrolyser and fuel cell is determined. Optimal charging and discharging power of plug-in electric vehicles is determined. Abstract: The plug-in electric vehicles and hydrogen storage systems containing electrolyzer, stored hydrogen tanks and fuel cell as energy storage systems can bring various flexibilities to the energy management problem. In this paper, selling price determination and energy management problem of an electricity retailer in the smart grid under uncertainties have been proposed. Multiple energy procurement sources containing pool market, bilateral contracts, distributed generation units, renewable energy sources (photovoltaic system and wind turbine), plug-in electric vehicles and hydrogen storage systems are considered. The scenario-based stochastic method is used for uncertainty modeling of pool market prices, consumer demand, temperature, irradiation and wind speed. In the proposed model, the selling price is determined and compared by the retailer in the smart grid in three cases containing fixed pricing, time-of-use pricing and real-time pricing. It is shown that the selling price determination based on real-time pricing and flexibilities of plug-in electric vehicles and hydrogen storage systems leads to higher expected profit. The proposed model is formulated as mixed-integer linear programming that can be solved under General Algebraic Modeling System. To validate the proposed model, three types of selling price determination under four case studies are utilized and the results are compared.